Nexus Green Finance dan Green Government dalam Mitigasi Perubahan Iklim: A Systematic Literature Review - Nur Febby Sagala; Nayra Jabrika Putri; Grisella Inggrid Ariesta; Rosalina Zita Pigome; Arina Romaina; Ardieansyah Ardieansyah; Luthfi Azhari (Pusat Riset dan Inovasi Nasional, 2026)
The global transition toward a low-carbon economy faces a significant financing gap, especially in Emerging Markets and Developing Economies (EMDEs), making Green Finance (GF) a crucial mechanism whose effectiveness depends heavily on institutional quality and governance. This study presents a Systematic Literature Review (SLR) of 90 peer-reviewed articles published between 2020–2025 sourced from Scopus and Web of Science, analyzed using PRISMA guidelines, VOSviewer bibliometrics, and narrative synthesis. The findings reveal three main research clusters: the effectiveness of GF instruments and green innovation, the moderating role of institutional quality and environmental governance, and the development of green financial markets and policies. Across the literature, GF consistently demonstrates a mitigating effect on CO₂ emissions; however, this impact is not automatic and is strongly strengthened by high-quality governance, including regulatory effectiveness and rule of law, which reduce investment risks and curb greenwashing. Major research gaps identified include an overconcentration of studies in China, the absence of standardized indicators for GF and Green Government (GG), and limited micro-level evidence from other developing regions such as ASEAN. Overall, this review highlights the need for integrated policy approaches that simultaneously advance green financial development and reinforce environmental governance.